QuantiFERON-TB performance enhanced by novel Mycobacterium tuberculosis-specific antigens. Issue 2 (19th November 2015) - Losi, Monica; Knights, Ashley J.; Mariani, Francesca; Altieri, Alfonso M.; Paone, Gregorino; Loxton, Andre G.; Chegou, Novel N.; Kenneth, John; Alma, Mario G.; Colizzi, Vittorio; Walzl, Gerhard; Saltini, Cesare; et al.
One of the most significant developments in the diagnosis of tuberculosis (TB) infection has been the introduction of whole-blood based interferon-γ release assays (IGRAs) [1–3]. IGRAs, commercially available as QuantiFERON-TB Gold In-Tube test (QFT) (QIAGEN, Germantown, MD, USA) and T-SPOT.TB (Oxford Immunotec Ltd, Abingdon, UK), are based on the detection of a T-cell immune response towards RD1 antigens (ESAT-6 and CFP-10), with the addition of the TB7.7 antigen for the QFT only [1]. IGRAs are endowed with great specificity, as the antigens used are almost exclusively expressed by the Mycobacterium tuberculosis (MTB) complex, but not Mycobacterium bovis bacille Calmette–Guerin (BCG) [1–3]. However, the diagnostic sensitivity of IGRAs can be improved (75–85% in HIV-negative active TB patients) especially in countries with a high TB burden [3]. Novel Mycobacterium tuberculosis antigens from macrophage infection model improve performance of QuantiFERON-TB http://ow.ly/TaqTO